Leadership Representation and Managerial Practices in Nollywood Films: Insights for Organizational Behaviour - Isaac Zeb-Obipi; Perpetua Ogechi Vitalis (PT Agung Media Publisher, 2026)
This study examines how leadership is represented in contemporary Nollywood films and explores its implications for organizational behaviour and managerial practice. While leadership has been extensively investigated in organizational and corporate settings, limited attention has been paid to cinematic narratives as culturally embedded sources of managerial knowledge, particularly within the African context. Using a qualitative comparative content analysis, the study analyzes four influential Nollywood films The CEO (2016), Lionheart (2018), The Last Flight to Abuja (2012), and 30 Days in Atlanta (2014). These films were purposively selected because they portray diverse organizational environments, leadership challenges, and decision-making processes. The findings reveal four dominant leadership representations namely transformational leadership that promotes innovation and employee empowerment, authoritarian leadership characterized by centralized crisis decision-making, participative leadership emphasizing collaboration and stakeholder engagement, and relational leadership that strengthens trust and interpersonal influence. The study further demonstrates that managerial effectiveness in the films is shaped by cultural values, organizational context, and leaders' ability to balance authority with participation. These cinematic narratives extend beyond entertainment by providing practical illustrations of leadership behaviour, conflict management, strategic decision-making, and organizational resilience. The study contributes to the business and management literature by positioning Nollywood films as valuable qualitative resources for understanding culturally grounded leadership practices in emerging economies.